LARYNX DISEASES - Yu.L. Soldatskiy (Union of pediatricians of Russia, 2008)
The author completes a series of publications devoted to the pathology of the upper respiratory passages among children. The article highlights the chronic pathology of larynx and trachea - laryngitis, relapsing respiratory papillomatosis, as well as acquired laryngostenosis and scabbard tracheae. Special attention is given to the problems of the modern diagnostics assisted by the up to date equipment and choice of the adequate tactics for the treatment of such patients.Key words: chronic laryngitis, relapsing respiratory papillomatosis, acquired laryngostenosis and scabbard tracheae, diagnostics, treatment.